The origin and recharge conditions of groundwater in Farafra Oasis, Western Desert, Egypt - Ameer Aziz; Hassan S. Sabet; Saad Y. Ghoubachi; Usama A. Abu Risha (Scientific African, 2022)
Farafra Oasis is considered as one of the most promising areas for future agricultural development in Egypt. The current research implements an integrated hydrogeologic and hydrogeochemical approaches to investigate the origin and recharge conditions of groundwater in Farafra Oasis. The main aquifer in the oasis is the artesian Nubian Sandstone which is overlain by the Khoman fractured limestone in the north and Dakhla shale in the south of the study area. The stable isotopes show that the groundwater of the Khoman aquifer is in reality Nubian Sandstone groundwater with head higher than the base of the Khoman Limestone. In some areas springs and flowing wells used to exist. In this work, the Nubian Sandstone aquifer is subdivided into three units (A and C) separated by a thick clay layer (unit B) that reaches 300 m thick. Unit A and the overlying limestone aquifer are hydraulically connected and can be regarded as one hydrogeologic unit. This is because the area is affected by sets of faults associated with fractures and joints. Therefore, we found that the salinities of these two aquifers are similar and range between 380 and 591 ppm. The groundwater salinity of the deep unit (C) reaches max to 242 ppm. The results reveal that the groundwater is of paleo-meteoric origin affected by hydrothermal solutions either by direct mixing or by interacting with the hydrothermally affected rocks as deduced from the direct relationship of the groundwater iron and oxygen-18 contents. Recharge occurred during heavy pluvial periods as can be deduced from the strongly depleted deuterium (2H) and oxygen-18 (18O). The impact of evaporation on the recharge water is evidenced by the direct relationship between the groundwater chloride and stable isotope contents.